A Comprehensive Greenhouse Gas Mitigation Strategy for The Netherlands - Batini, Nicoletta (IMF Working Papers; Working Paper, 2021)
The Netherlands has ambitious greenhouse gas emission reduction targets for the future - to cut them by 49 percent below 1990 levels by 2030 and 95 percent by 2050. These targets and the likely new EU-wide targets under the recent EU Green Deal entail a rapid acceleration in decarbonization. This paper discusses the government's mitigation strategy and advances several recommendations to complement and reinforce that strategy and to achieve better alignement of the effective carbon prices across sectors. The paper discusses alternatives to make the recently-introduced industry carbon levy more effcient and recomends the use of revenue-neutral feebate schemes in industry, transportation, buildings, and agriculture. For power generation, it recommends eliminating taxes on residential and industrial electricity, supplementing the coal phaseout plan with an increase in the CO2 emissions floor price. The impacts of these reforms on consumption would be low and relatively evenly split across the income distribution.